(untitled) (Mustansiria Dental Journal, 2018)
Background: The using of devices that emitted electromagnetic radiation has been limited in many healthcare centers to prevent interference with medical devices. The purpose of this in vitro study was to evaluate the effect of Wi-Fi Router (Tenda FH456) on working length determination using electronic apex locator (NSK-iPex II) in the presence of network connection with tablet (GT-N800) or not. Materials and methods: Twenty-five intact teeth with a single root were sectioned at the cementoenamel junction. Visually, roots were examined under stereomicroscope (X20) and the working length was determined using a size 15 K-file. The effect of Tenda Wi-Fi router on accuracy of electronic working length measurement of electronic apex locator (iPex II) was determined in this study in closed room under 5 conditions (without router and tablet, with router in different distances 1 meter and 3 meters from electronic apex locator, with router and connected with tablet in different distances 1 meter and 3 meters from electronic apex locator). The electronic working length was measured 3 times per canal under each condition. The data were compared using analysis of variance. Results: The mean of working length measured under microscope was (13.30), and the mean of working length by electronic apex locator was (13.14) while the mean values of working length in different conditions was fixed (13.12). Analysis of variance test (ANOVA) showed non-significant difference among working length measurements in different conditions (P-value ≥ 0.05). Conclusion: Within the limitations of the present study, stability and reliability of iPex II apex locator in measurement of electronic working length where not influenced when placed in (1M, 3M) from Wi-Fi router and active Tablet (connected to network by Wi-Fi and streaming online videos). During root canal therapy, active Tablet can be used in the dental operatory without the fear of causing electromagnetic interference in electronic working length determination.